Discrepancy in student peer and self-evaluations: a predictor of team performance? - Marmet, Matthew D. (Journal of Management and Business Education, 2022)
Performance prediction and evaluation (rating) have been investigated by psychologists for years. One aspect of performance description that has increased in popularity is multisource feedback. This process typically involves a focal person receiving feedback on their performance from the perspectives of others. Additionally, these multisource feedback systems call on this focal person to rate their own performance, so an evaluation of the discrepancy between self and others’ ratings can be made. The current study aims to assess the impact of self-other rating congruence in an academic setting. Specifically, can team performance be predicted by the level of agreement between self and others’ ratings? The magnitude of the discrepancy between self and others’ ratings on a student peer evaluation form was appraised, and the correlation between discrepancy magnitude and team performance on a final project was assessed. Initial data analysis yielded results contrary to the proposed hypothesis, but also called into question the overall utility of the evaluation process itself.